(untitled) (Journal of the College of Basic Education, 2022)
A field experiment was conducted in the botanical garden at the College of Education for Pure Sciences during the winter growing season (2014-2015) to study the effect of tryptophan at the following concentrations 5, 10, 15, and 20 mg. L-1 in the growth and yield of wheat plant (Triticum aestivum L.), the results showed a significant increase in all phenotypic and physiological traits such as plant height, number of leaves, number of combs, total chlorophyll a and b concentration, shoot length, spike length and weight, leaf area Flag, plant dry weight, absolute growth rate and percentage of protein in seeds compared with control plants.